A pilot study of the eccentric decline squat in the management of painful chronic patellar tendinopathy. Issue 4 (23rd July 2004) - Purdam, C R; Jonsson, P; Alfredson, H; Lorentzon, R; Cook, J L; Khan, K M
Abstract : Objectives: This non-randomised pilot study investigated the effect of eccentric quadriceps training on 17 patients (22 tendons) with painful chronic patellar tendinopathy. Methods: Two different eccentric exercise regimens were used by subjects with a long duration of pain with activity (more than six months). ( a ) Nine consecutive patients (10 tendons; eight men, one woman; mean age 22 years) performed eccentric exercise with the ankle joint in a standard (foot flat) position. ( b ) Eight patients (12 tendons; five men, three women; mean age 28 years) performed eccentric training standing on a 25° decline board, designed to increase load on the knee extensor mechanism. The eccentric training was performed twice daily, with three sets of 15 repetitions, for 12 weeks. Primary outcome measures were ( a ) 100 mm visual analogue scale (VAS), where the subject recorded the amount of pain during activity, and ( b ) return to previous activity. Follow up was at 12 weeks, with a further limited follow up at 15 months. Results: Good clinical results were obtained in the group who trained on the decline board, with six patients (nine tendons) returning to sport and showing a significantly reduced amount of pain over the 12 week period. Mean VAS scores fell from 74.2 to 28.5 (p  =  0.004). At 15 months, four patients (five tendons) reported satisfactory results (mean VAS 26.2). In the standard squat group the results were poor, with only one athlete returning to previous activity. Mean VAS scores in this group were 79.0 at baseline and 72.3 at 12 weeks (p  =  0.144). Conclusion: In a small group of patients with patellar tendinopathy, eccentric squats on a decline board produced encouraging results in terms of pain reduction and return to function in the short term. Eccentric exercise using standard single leg squats in a similar sized group appeared to be a less effective form of rehabilitation in reducing pain and returning subjects to previous levels of activity.